2012
DOI: 10.1007/s00264-011-1474-5
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous pinning of three- or four-part fractures of the proximal humerus in elderly patients in poor general condition: MIROS® versus traditional pinning

Abstract: Purpose Elderly subjects often have fractures of the proximal humerus, which may be difficult to manage in patients in poor general condition. The MIROS is a new percutaneous pinning device allowing correction of angular displacement and stable fixation of fracture fragments. We evaluated the results of percutaneous fixation of three-or four-part fractures of the proximal humerus of patients in the American Society of Anesthesiologists physical status three or four treated either with MIROS or traditional perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 22 publications
1
35
1
1
Order By: Relevance
“…Patient characteristics and injury mechanisms in our study were similar to previous studies; more commonly being an elderly female sustaining trauma to shoulder following a trivial fall [11][12][13][14] . In our study, the mean time to radiological union was 2 months, which is comparable to previous studies on use of external fixator in proximal humerus [15,16] . There was only one incidence of pin migration and in none of the cases there was pin loosening inspite of early mobilization.…”
Section: Resultssupporting
confidence: 89%
“…Patient characteristics and injury mechanisms in our study were similar to previous studies; more commonly being an elderly female sustaining trauma to shoulder following a trivial fall [11][12][13][14] . In our study, the mean time to radiological union was 2 months, which is comparable to previous studies on use of external fixator in proximal humerus [15,16] . There was only one incidence of pin migration and in none of the cases there was pin loosening inspite of early mobilization.…”
Section: Resultssupporting
confidence: 89%
“…Carbone et al reported 2-year outcomes after traditional percutaneous pinning (TPP) and a special technique of percutaneous pinning (called MIROS 1 ) similar to an external fixator in elderly patients and poor general health conditions (American Society of Anaesthesiologists (ASA) stage 3 or 4) for three-and four-part fractures [45]. The CS for three-part fractures was 53 points in the TPP group and 62 points in the MIROS 1 group, whereas for four-part fractures it was 50 points and 58 points, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Previous reports on proximal humerus fractures treated with external fixation found a 6%-19% infection rate. [15][16][17] The 39.1% infection rate in the current study is based on clinical diagnosis with only partial confirmation through positive cultures. These liberal criteria may be responsible for the high rate compared with previous reports.…”
Section: Discussionmentioning
confidence: 99%